Online Stock Trading in India: An Empirical Investigation - Walia, Nidhi; Kumar, Ravinder (Indian Journal of Marketing, 2007)
With IT fuelling Indian economy, Internet is adopted as effective tool in catalyzing the business activities. Latest developments in information technology have altogether changed the business done traditionally. As financial system is becoming more complex it has become need of the hour where investors should comprehend the data and understand recent intricacies of online trading. In Indian context e- trading is relatively new phenomenon, which has yet to gain some significant meaning. In the past investors have no other option to get market information except to contact their local broker? But Internet trading in stock market is becoming medium of exchange whereby investor can order stock exchange on simple mouse click sitting at his place. Keeping in view current market requirement an attempt has been made in this research paper to analyze current status of online trading in Indian scenario. Facts highlighted in this study clearly reveal that although online trading is picking up its speed to tap investors yet it is expected to adopt creative strategies to lure customers from physical trading to net trading.